MANAGEMENT OF INTRACRANIAL HIGH PRESSURE ON STROKE: A NARRATIVE REVIEW - KRISTINA ELISABET, FRANSISCA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Intracranial pressure (ICP) is a dynamic and fluctuating pressure within the cranial vault influenced by cerebrospinal fluid (CSF), brain tissue, and blood. Any increase in the volume of its contents will increase the pressure within the cranial vault. As a response to ICP, compensation begins by the movement of CSF from the ventricle to cerebral subarachnoid space and increases CSF absorption. Increased ICP is a state of neurological emergency caused by various neurological injuries. It is associated with poor outcomes, including traumatic brain injury, large acute ischemic stroke, intracerebral hemorrhage, or even death. This article aims to review the symptoms and signs of increased ICP, particularly on infarction stroke and hemorrhagic stroke condition, how the therapeutic goals of the treatment strategies, and pharmacological or non-pharmacological management to mitigate the elevation of ICP on stroke.